2022
DOI: 10.29040/ijebar.v6i1.4453
|View full text |Cite
|
Sign up to set email alerts
|

Risk Attitudes, Mental Accounting and Overconfidence in Investment Placement Decision During and Post Covid-19

Abstract: The Small and Medium Enterprises is the main pillar the people's economy. SME investment decisions related to how entrepreneurs place their funds is a very determining factor in company performance. The purpose of this study is to analyze and explain: 1) The influence of risk attitudes on company performance through decisions on the placement of working capital funds for small and medium enterprises (SMEs), 2) The effect of risk attitudes on company performance in SMEs 3) the effect of working capital fund pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is supported by Armansyah (2021); Anggini (2019) dan Santi, Sahara & Kamaludin (2019) show that mental accounting has a significant positive effect on investment decisions. Different results were shown by Novandalina, Ernawati & Adriyanto (2022) that mental accounting did not have a significant effect on investment decision making.…”
Section: Introductionmentioning
confidence: 79%
“…This is supported by Armansyah (2021); Anggini (2019) dan Santi, Sahara & Kamaludin (2019) show that mental accounting has a significant positive effect on investment decisions. Different results were shown by Novandalina, Ernawati & Adriyanto (2022) that mental accounting did not have a significant effect on investment decision making.…”
Section: Introductionmentioning
confidence: 79%
“…The delay of financial reporting may attribute to external auditors. Novandalina, Ernawati and Budiyono (2022) found that audit quality and audit opinion about financial statements had no effect on the timeliness of the presentation of financial statements. Efobi and Okougbo (2014) also found that audit type has no influence the timeliness of financial reporting because auditors cannot change the timeliness of financial reports without their client.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Efobi and Okougbo (2014) and Hoang, Pham, Thalassinos, and Le (2022) found a negative relationship between the firm size, leverage, performance, and timeliness of financial reporting, while firm age was positive. While Aigienohuwa andEzejiofor (2021), andNovandalina, Ernawati, andBudiyono (2022) found that leverage had no effect on the timeliness of financial reporting.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…A pandemic has caused enormous changes in society, almost all of which have a negative impact on individual and business income (Tonnoir et al, 2021). A study of the various negative effects of the pandemic Covid-19 on investment decisions and attitudes among millennial generation Y is critical (Novandalina et al, 2022), because it has affected investment and financial activity. Investment decision behavior describes how investors gather and manage information to make an investment decision (Slovic et al, 1972).…”
Section: Introductionmentioning
confidence: 99%